Ultrasructural organization of inflammatory infiltrate’s cells in skin of patients with psoriasis treated by NB-UVB (311 nm). - Babanin, V. A.; Pritulo, O. A.; Filonenko, T. G.; Bisuk, Yu. A. (Морфологія / Morphologia / Morfologìâ, 2013)
Aim of study: studying of ultrastructural features of immunocompetent cells in the inflammatory infiltrate of derma in a patient with psoriasis under the influence of NB-UVB (311 nm) therapy. Material for transmission and scanning electron microscopy - skin biopsies, taken from 40 patients with plaque psoriasis, divided by into 2 groups according to treatment scheme. 1-st group – 32 patients with NB-UVB (311 nm) therapy, 2-nd group – 8 patients with standard treatment. On 21 day of treatment patient of 1group were divided into 4 subgroup according to regression of PASI index and application of suberythmogenic and erythmogenic treatment strategies. The result’s analysis of transmission and scanning electron microscopy of skin biopsies with plaque psoriasis allowed to identified ultrastructural and stereoscopical features of immune inflammation, with different functional load. On 1-st day of investigation low-functional macrophages with small amount of phagosomes, lysosomes and activated lymphocytes with a wide cytoplasm around the nucleus and a lot of organells were dominated. On 21-st day of NB-UVB therapy ratio between low- and high-functional macrophages was restored. Macrophages located in contact with apoptotic lymphocytes. It should be noted that in subgroups of patients with a high index regression PASI macrophages which actively phagocyte lymphocytes was present. At 12 weeks in patients with regression PASI index less than 50% and using a strategy suberythmogenic NB-UVB (311 nm) therapy, degenerative forms of macrophages with presents of broad craters on the surface of a cell become the main feature.